DRAM-1 encodes multiple isoforms that regulate autophagy - Yen Mah, Li (Landes Bioscience, 2012)
Macro(autophagy) is a cellular mechanism which delivers cytoplasmic constituents to lysosomes for degradation. Due to its role in maintaining cellular integrity, autophagy protects against various diseases including cancer. p53 is a major tumor suppressor gene which can modulate autophagy both positively and negatively. p53 induces autophagy via transcriptional activation of damage-regulated autophagy modulator (DRAM-1). We report here that DRAM-1 encodes not just one mRNA, but a series of p53-inducible splice variants which are expressed at varying levels in multiple human and mouse cell lines. Two of these new splice variants, termed SV4 and SV5, result in mature mRNA species. Different from ‘full-length’ DRAM-1 (SV1), SV4 and SV5 do not localize to lysosomes or endosomes, but instead partially localize to peroxisomes and autophagosomes respectively. In addition, SV4 and SV5 can also be found co-localized with certain markers of the endoplasmic reticulum. Similar to SV1, SV4 and SV5 do not appear to be inducers of programmed cell death, but they do modulate autophagy. In summary, these findings identify new autophagy regulators that provide insight into the control of autophagy downstream of p53.